OCCURRENCE AND DEVELOPMENT OF IRRIGATION SYSTEM - V.Y. Isaqov; H.Nazarov; F.X. Yoqubjonov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article covers the emergence, formation and development of irrigation systems in the Fergana Valley, which is considered one of the Centers of the world peasant civilization. The history of the occurrence and development of irrigation and irrigation systems is divided into 3 main stages. The first stage included the period from the Neolithic to the end of the bronze and the beginning of the Iron. During this period, Lemon irrigation was formed in the foothills and in the river banks of the plains. The skills of mastering and using simple methods of water management, such as winding fields with marzas, expelling excess water into lowlands, cleaning networks that have become turbid, have been formed. The second stage e.o. B from the III century.e. Siege the range until the IV century. This stage is characterized by the restoration of small irrigation systems with a mesh of water collection in the foothills, the transition to the application of artificial irrigation methods, such as the construction of ponds as a pond in the places of pouring shadows. The third stage began with the restoration of relatively complex irrigation systems in the foothills. Such systems consist of special head structures and a number of trunk channels, and in the upper distribution node, solid adjoins are fixed. The devices for raising water to higher regions have been mastered. Irrigation systems, facilities and methods have been perfected over the centuries, using areals increasingly.